Energy Conservation - Zain Ahmed, Azni (IntechOpen, 2012)
This book covers the areas of fundamentals in energy conservation and its applications in selected industries. There are nine chapters in this book which have been written by leading experts in energy from all over the world. The topics range from energy fundamentals from cosmic radiation, tidal waves and dams. The chapters examine the potential of utilizing energy from sustainable resources and how energy consumption may be conserved from various new technologies. The contents of this book include space energy, barotropic and baroclinic tidal energy, understanding energy conservation in biological context, Earth shelters, hydro power, biofuel from groundnut oil and low energy consumption in industrial production. This book is suitable as a reference for students, educators, researchers, scientists, engineers and energy practitioners. It will also be a useful for the understanding of energy fundamentals, design and applications.